3D printing‐enabled advanced electrode architecture design. Issue 3 (5th May 2021) - Chu, Tiankuo; Park, Soyeon; Fu, Kun (Kelvin)
Abstract: A high‐performance energy storage device plays an important role in controlling carbon emissions. The emerging additive manufacturing techniques bring a great revolution of electrode fabrication process and promote the performance of energy storage devices through the advanced electrode architecture design. In this paper, recent studies on the three‐dimensional (3D)‐printed electrode with advanced architecture have been mainly reviewed, including interdigitated structure, through‐thickness aligned structure, hierarchical porous structure and fiber and fibric structure of electrodes, and expectations for the development of novel advanced electrode architecture generated and optimized by computational simulation and machine learning. The strategy of advanced electrode architecture design and fabrication enabled by the 3D printing technique represents a promising direction toward future energy storage devices with high electrochemical and mechanical performance. Abstract : Energy storage devices have been developed for high energy density and power density with a long lifetime. Three‐dimensional (3D) printing is a prominent technology for manipulating the device's electrode structure design to provide better performance. This review summarizes the critical role of 3D printing techniques in advanced electrode architecture design and fabrication and shares our thoughts on future 3D printing electrode development.